Almost all known sauropod necks are incomplete and distorted - Taylor,Michael P (PeerJ PrePrints, 2015)
Sauropods are familiar dinosaurs, immediately recognisable by their great size and long necks. However, their necks are much less well known than is usually assumed. Very few complete necks have been described in the literature, and even important specimens such as the Carnegie Diplodocus and Apatosaurus, and the giant Berlin brachiosaur, in fact have imperfectly known necks. In older specimens, missing bone is often difficult to spot due to over-enthusiastic restoration. Worse still, even those vertebrae that are complete are often badly distorted – for example, in consecutive cervicals of the Carnegie Diplodocus CM 84, the aspect ratio of the posterior articular facet of the centrum varies so dramatically that C14 appears 35% broader proportionally than C13. Widespread incompleteness and distortion are both inevitable due to sauropod anatomy: large size made it almost impossible for whole individuals to be preserved because sediment cannot be deposited quickly enough to cover a giant carcass; and distortion of presacral vertebrae is common due their lightweight pneumatic construction. This ubiquitous incompleteness and unpredictable distortion compromise attempts to determine habitual neck posture and range of motion by modelling articulations between vertebrae.
Keywords: Sauropod; Dinosaur; Preservation; Neck; Cervical vertebrae